Akibat Hukum Penyalahgunaan Wewenang Administrasi Pejabat Pemerintahan yang Menimbulkan Kerugian Keuangan Negara - Henny Juliani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
AbstractIn a governmental implementation, government officers execute the function of regulating, serving, developing, empowering, and protecting to create people's welfare. In the implementation of the functions, government officers have the authority to make a decision and action. Therefore government officers are forbidden abusing their authority. Supervision on authority abuse of government officers is conducted by APIP. The result of supervision by APIP is comprised of without mistakes, with administrative mistakes, or with an administrative mistake that potentially causes state financial loss. Legal consequences of government officers on authority abuse, which cause state financial loss due to maladministration, become the responsibility of the government officers themselves, respectively, by returning the same amount of state financial loss due to authority abuse. Based on the APIP supervision report, the government officers accused of doing authority abuse, may request to be assessed to find out whether there is authority abuse or not when the government officers decree and execute their policies, before it becomes criminal proceeding. The request is proposed to PTUN based on Regulation of Royal Court Number 4 of 2015. Keywords: Administrative Authority Abuse, State Financial Loss AbstrakDalam penyelenggaraan pemerintahan, pejabat pemerintahan melaksanakan fungsi pengaturan, pelayanan, pembangunan, pemberdayaan, dan perlindungan bagi peningkatan kesejahteraan rakyat. Dalam melaksanakan fungsi tersebut pejabat pemerintahan memperoleh wewenang untuk mengambil keputusan dan/atau tindakan, oleh karena itu maka pejabat pemerintahan dilarang menyalahgunakan wewenang. Pengawasan terhadap larangan penyalahgunaan wewenang tersebut dilakukan oleh APIP. Hasil pengawasan APIP berupa: tidak terdapat kesalahan, terdapat kesalahan administratif, atau terdapat kesalahan administratif yang menimbulkan kerugian keuangan negara. Akibat hukum pejabat pemerintahan terhadap penyalahgunaan wewenang yang menimbulkan kerugian keuangan negara karena adanya kesalahan administratif/maladministratif menjadi tanggung jawab pribadi dengan mengembalikan kerugian keuangan negara yang ditimbulkan sebagai akibat dari perbuatan yang dia lakukan. Berdasarkan hasil pengawasan APIP tersebut, pejabat pemerintahan yang dianggap telah melakukan penyalahgunaan wewenang, dapat mengajukan permohonan penilaian unsur ada tidaknya penyalahgunaan wewenang dalam mengeluarkan keputusan dan/atau tindakan kepada Peradilan Tata Usaha Negara berdasarkan Peraturan Mahkamah Agung Nomor 4 Tahun 2015, sebelum adanya proses pidana. Kata Kunci: Penyalahgunaan Wewenang Administrasi, Kerugian Keuangan Negara